2000
DOI: 10.1080/713654980
|View full text |Cite
|
Sign up to set email alerts
|

Genetic effects of ageing on fertility and hatchability in the first laying cycle of three White Leghorn strains and their two-way crosses

Abstract: 1. Fertility and hatchability of 3 White Leghorn strains and their 2-way crosses were examined in the 1st laying cycle to evaluate the effects of ageing on mean heterosis, reciprocal effects, additive (A), Z-chromosomne (Z) and heterotic effects (H), as well as on their variances. 2. Fertility and hatchability were evaluated at 37, 47 and 70 weeks of age for hens housed 1 per cage in a randomised block design. The mean heterosis was significant over time and increased with advancing age for both traits. Recipr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…It tends to follow a pattern similar to egg production, with an initial increase from start of lay to a peak that is sustained for several weeks followed by considerable decline as the birds age (Heier and Jarp, 2001). Ledur et al (2000) reported substantial changes in additive and nonadditive genetic components of hatchability related to aging. This has led to calls to model the trait with a random regression model that takes into account the longitudinal nature of the trait and changes of variance components over time (Bennewitz et al, 2007).…”
Section: Introductionmentioning
confidence: 93%
“…It tends to follow a pattern similar to egg production, with an initial increase from start of lay to a peak that is sustained for several weeks followed by considerable decline as the birds age (Heier and Jarp, 2001). Ledur et al (2000) reported substantial changes in additive and nonadditive genetic components of hatchability related to aging. This has led to calls to model the trait with a random regression model that takes into account the longitudinal nature of the trait and changes of variance components over time (Bennewitz et al, 2007).…”
Section: Introductionmentioning
confidence: 93%
“…Due to the higher embryonic mortality in CL crosses, the hatchery efficiency is lower than in other crosses. Ledur et al (2000) obtained 94-97% fertility and 86.65-90.60% hatchability in their crosses in White Leghorn lines of different ages. The fact that it was found to be lower than the findings of this study may be due to the age factor as well as the difference in care and feeding conditions.…”
Section: Discussionmentioning
confidence: 97%
“…It is generally known that hatchability and fertilisation rate are important reproductive performance indicators of breeder hens (Abend et al, 1977). It has been reported that the hatching effect of breeder hens in the late stages of laying may be poorer than that in the peak laying period, but there will be no significant difference in fertilisation rate (Ledur et al, 2000). Furthermore, a previous study had revealed that as the dose of daidzein supplementation increases, the hatching rate and fertilisation rate of breeder hens will show a linear trend increase, and it was believed to be related to the level of E2 (Lu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Based on these measurements, feed conversion rate (FCR) was determined according to the method of Saleh (Saleh, 2013). In the last 3 days of the formal experiment, we obtained 90 fertilised eggs in total from each treatment to evaluate fertility and hatchability, which was according to the method of Ledur (Ledur et al, 2000). All collected hatching eggs were incubated in the same incubator.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation